Evaluation of the status quo of polyphenols analysis: Part I—phytochemistry, bioactivity, interactions, and industrial uses. Issue 6 (31st August 2020) - Silva, Ana Sanches; Reboredo‐Rodríguez, Patricia; Süntar, Ipek; Sureda, Antoni; Belwal, Tarun; Loizzo, Monica Rosa; Tundis, Rosa; Sobarzo‐Sanchez, Eduardo; Rastrelli, Luca; Forbes‐Hernandez, Tamara Y.; Battino, Maurizio; Filosa, Rosanna; et al.
Abstract: Phytochemicals, especially polyphenols, are gaining more attention from both the scientific community and food, pharmaceutical, and cosmetics industries due to their implications in human health. In this line, lately new applications have emerged, and of great importance is the selection of accurate and reliable analytical methods for better evaluation of the quality of the end‐products, which depends on diverse process variables as well as on the matrices and on the physicochemical properties of different polyphenols. The first of a two‐part review on polyphenols will address the phytochemistry and biological activities of different classes of polyphenols including flavonoids, lignans and flavanolignans, stilbenoids, tannins, curcuminoids, and coumarins. Moreover, the possible interactions of polyphenols and current and potential industrial applications of polyphenols are discussed.